Penyuluhan Bahaya Gangguan Stres Pasca Pandemi Dalam Lingkup Rumah Tangga di Masyarakat Pesisir di Baubau - Ardiansyah Ardiansyah; Fikih Fikih; Arman Ode; Ade Erdin (Jurnal Pengabdian Masyarakat Nusantara, 2021)
The COVID-19 pandemic has significantly altered the lives of many people, particularly in the social and economic domains. Coastal communities, which heavily rely on sea-based economic activities such as fishing, tourism, and maritime trade, have faced severe disruptions due to the pandemic. This has led to economic instability and increased psychological stress within these communities. One of the most notable effects has been the rise in post-pandemic stress disorder (Post-Traumatic Stress Disorder or PTSD) among household members. The persistent stress experienced by individuals, especially in coastal households, is having a detrimental effect on both psychological and social well-being. Stressors, including financial insecurity, social isolation, and health concerns, are exacerbating the strain on family relationships and community dynamics. The goal of this research is to provide targeted education on the dangers of post-pandemic stress disorders, particularly focusing on coastal communities. Through an educational approach, this research aims to raise awareness about the symptoms, causes, and consequences of PTSD. The program also seeks to provide practical strategies and coping mechanisms that households can use to manage stress and maintain psychological resilience in the post-pandemic environment. The findings of this study are expected to contribute to community-based mental health interventions, enhance family stability, and improve overall well-being in these vulnerable populations